Launch of the Ethiopian Digital AgroClimate Advisory Platform (EDACaP) Progress Report on EDACaP Development and Hosting - Ahmed, Jemal Seid; Tesfaye, Kindie; Sibiry Traoré, Pierre C. (2019)
This brief outlines progress achieved with the establishment of the Ethiopian Digital AgroClimate Advisory Platform (EDACaP) under the CCAFS project P263 (Regional and national engagement, synthesis and strategic research) with support from P1605 (Capacitating African Stakeholders with Climate Advisories and Insurance Development). EDACaP aims to build farmers' resilience through agro-climate advisories that digitally integrate climate, soil, crop and agronomic data and are delivered through SMS, IVRS and radio to development agents and farmers in local languages. It builds on a partnership between the Ethiopian Institute of Agricultural Research (EIAR), the Ministry of Agriculture (MoA), the National Meteorological Agency, CIAT, ILRI, CIMMYT with additional support from ICRISAT, IRI, and University of Florida.